A Cylindrical Conformal Textile Antenna With Omnidirectional Radiation Pattern - Renhang Liang; Zhixi Liang; Yuanxin Li; Yiming Zhang; Shaoyong Zheng (IEEE Access, 2024)
A novel textile antenna is proposed to produce an omnidirectional radiation pattern. It can be integrated with clothes as a wristband due to its cylindrical conformal design. The antenna has a resonant cavity fabricated from conductive fabric and filled with cotton fabric. Three edges of the cavity are short-circuited with conductive threads and coupled-fed by a patch coupler fabricated with flexible printed circuit (FPC). Theoretical analysis shows that the proposed antenna is equivalent to a magnetic current loop, which produces a dipole-like radiation pattern when its radius is less than 0.4 wavelengths. Simulated results show that the antenna produces a low specific absorption rate (SAR) when it is loaded on human tissues. Measured results show a bandwidth from 2.36 GHz to 2.52 GHz with an omnidirectional radiation pattern. The peak gain varies between 0.6 dBi and -0.6 dBi within the bandwidth. The small thickness and simple structure of the proposed antenna make it a good candidate for wearable applications.